2017
DOI: 10.1097/ana.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Equiosmolar Solutions of Hypertonic Saline and Mannitol Do Not Impair Blood Coagulation During Elective Intracranial Surgery

Abstract: The use of 5 mL/kg of equiosmolar solutions of 3% HS and 20% mannitol applied to reach a brain relaxation during elective craniotomy does not induce coagulation impairment as evidenced by ROTEM and standard coagulation tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Similar to the current findings, in two recent studies in people undergoing elective craniotomy or suffering from traumatic brain injury, respectively, no difference in standard coagulation tests and ROTEM® analysis was found between patients administered 20% mannitol and those receiving 3% HTS [ 15 , 28 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to the current findings, in two recent studies in people undergoing elective craniotomy or suffering from traumatic brain injury, respectively, no difference in standard coagulation tests and ROTEM® analysis was found between patients administered 20% mannitol and those receiving 3% HTS [ 15 , 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…In consequence, the safety of using these agents in patients with ICH and intracranial hemorrhage remains unclear [ 4 , 11 , 13 ]. Previous in vitro studies in humans have demonstrated anticoagulant effects of both mannitol and HTS [ 9 , 14 ], although one clinical study failed to demonstrate any negative effect on hemostasis using either solution in patients undergoing elective intracranial surgery [ 15 ]. Similarly, in vitro studies in dogs demonstrated that both mannitol and HTS have negative effects on coagulation in a dose-dependent fashion, although in vivo studies in dogs in a clinical setting are lacking [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors concluded that, although the administration of hypertonic solutions reduced the levels of platelets and fibrinogen significantly, because of a dilutional effect, it was not enough to reduce MCF. 6 Another clinical study reported that CFT altered significantly from baseline after administration of mannitol alone as well as in combination with hydroxyethyl starch (HES) and MCF measured with FIBTEM did not change from baseline, but differed significantly between groups. 23 Nevertheless, as all ROTEM values remained within normal range, the authors also concluded that mannitol and HES can be safely administered in patients undergoing craniotomy for supratentorial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Although mannitol is a solution being infused daily to decrease intracranial pressure and improve surgical conditions during craniotomy, only few studies have evaluated the effect of mannitol on blood coagulation. [1][2][3][4][5][6] In vitro mannitol seems to interfere with blood coagulation by reducing clot strength at 10 and 20 vol% dilutions, 2 which is possibly a result from poor fibrin clot formation. 3 Data from animal studies have also shown that mannitol impairs coagulation in vitro in a dose-dependent manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation